Long-term outcome of endoscopic ultrasound-guided pelvic abscess drainage: a two-center series - Poincloux, Laurent; Caillol, Fabrice; Allimant, Christophe; Bories, Erwan; Pesenti, Christian; Mulliez, Aurélien; Faure, Frederic; Rouquette, Olivier; Dapoigny, Michel; Abergel, Armando; Giovannini, Marc (Endoscopy, 2017)
Background and study aim Endoscopic ultrasound (EUS)-guided pelvic abscess drainage has been reported but long-term data remain limited. This two-center study evaluated long-term outcome of EUS-guided pelvic abscess drainage. Patients and methods Between May 2003 and December 2015, 37 consecutive patients were treated for perirectal or perisigmoid abscesses via EUS-guided drainage using plastic or lumen-apposing metal stent (LAMS). Clinical success was defined as complete resolution of the abscess on follow-up computed tomography (CT) scan at 4 weeks with symptom relief. Long-term success was defined as abscess resolution without the need for surgery and without recurrence on long-term follow-up (> 12 months).Results Median abscess size was 60 mm (interquartile range 41 – 70). Causes were postsurgical (n = 31, 83.8 %) or secondary to medical conditions (n = 6, 16.2 %). EUS-guided drainage involved needle aspiration (n = 4), plastic stent placement (n = 29) or LAMS placement (n = 4 patients). Technical and clinical success was achieved in 37 patients (100 %; 95 % confidence interval [CI] 91 – 100) and 34 patients (91.9 %; 95 %CI 78 – 98), respectively (5 patients needed a second EUS-guided intervention within 14 days after drainage). One patient required surgery and one required best supportive care owing to persistent abscess. Early complications were perforation requiring surgery (n = 1), stent migration (n = 1), and rectal discomfort (n = 1). At a median follow-up of 64 months (IQR 19 – 81), two patients experienced abscess recurrence, at 3 and 12 months, respectively, and were treated surgically. Long-term success was achieved in 32 of 37 patients (86.5 %; 95 %CI 71 – 95). Conclusion EUS-guided drainage of pelvic abscess is safe, has good long-term outcome, and should be considered as an alternative to percutaneous and surgical drainage.